The glucotoxicity protecting effect of honokiol in human hepatocytes via directly activating AMPK - Liu, Hui; Luo, Wu; Liu, Jiazheng; Kang, Xincong; Yan, Jianming; Zhang, Tingting; Yang, Lan; Shen, Lu; Liu, Dongbo (Frontiers in Nutrition, 2022)
Sustained hyperglycemia caused glucotoxicity, which has been regarded as a contributor to hepatocytes damage in type 2 diabetes (T2D) and its metabolic comorbidities. Honokiol, a natural biphenolic component derived from dietary supplement Magnolia officinalis extract. The purpose of this study was to investigate the effects of honokiol on glucose metabolism disorder and accompanied by oxidative stress in hepatocytes with glucotoxicity and the underlying mechanisms. HepG2 cells were treated with glucosamines (18mM) to induce glucotoxicity, as a diabetic complications model in vitro. Honokiol significantly increased glucose consumption, elevated 2-NBDG uptake, and promoted GLUT2 translocation to the plasma membrane in glucosamine-treated HepG2 cells, indicating that honokiol ameliorate glucose metabolism disorder. Glucosamine-induced accumulation of ROS, loss of mitochondrial membrane potential were markedly reduced by honokiol, suggesting that honokiol alleviate glucotoxicity-induced oxidative stress. These effects were largely abolished by compound C, AMPK inhibitor, suggesting an AMPK activation-dependent manner of honokiol function on promoting glucose metabolism and mitigating oxidative stress. Molecular docking results revealed that honokiol could interact with the amino acid residues (His151, Arg152, Lys243, Arg70, Lys170 and His298) in the active site of AMPK. These findings provide new insights into the anti-diabetic effect of honokiol, which may be a promising agent for the prevention and treatment of T2D and associated metabolic comorbidities.